Biodiversity scale‐dependence and opposing multi‐level correlations underlie differences among taxonomic, phylogenetic and functional diversity. (25th October 2021) - Mirochnitchenko, Nadejda A.; Stuber, Erica F.; Fontaine, Joseph J.
Abstract: Aim: Biodiversity is a multi‐dimensional property of biological communities that represents different information depending on how it is measured, but how dimensions relate to one another and under what conditions is not well understood. We explore how taxonomic, phylogenetic, and functional diversity can differ in scale‐of‐effect dependence and habitat‐biodiversity relationships, and subsequently how spatial differences among biodiversity dimensions may arise. Location: Nebraska, United States. Taxon: Birds. Methods: Across 2016 and 2017, we conducted 2, 641 point counts at 781 sites. We modeled the occupancy of 141 species using Bayesian Bernoulli‐Bernoulli hierarchical logistic regressions. We calculated species richness (SR), phylogenetic diversity (PD) and functional diversity (FD) for each site and year based on predicted occupancy, accounting for imperfect detection. Using Bayesian latent indicator scale selection and multivariate modeling, we quantified the spatial scales‐of‐effect that best explained the relationships between environmental characteristics and SR, PD and FD. Additionally, we decomposed the residual between‐site and within‐site biodiversity correlations using our repeated measures design. Results: Although relationships between specific land cover types and SR, PD and FD were qualitatively similar, the spatial scales at which these variables were important in explaining biodiversity differed among dimensions. Between‐site residual biodiversity correlations were negative, yet within‐site biodiversity residual correlations were positive. Main conclusions: Our results demonstrate how spatial differences among biodiversity dimensions may arise from biodiversity‐specific scale‐dependent habitat relationships, low shared environmental correlations and opposing residual correlations between dimensions, suggesting that single‐scale and single‐dimension analyses are not entirely appropriate for quantifying habitat‐biodiversity relationships. After accounting for shared habitat relationships, we found positive within‐site residual correlations between SR, PD and FD, suggesting that habitat change over time influenced all biodiversity dimensions similarly. However, negative between‐site residual correlation among biodiversity dimensions may indicate trade‐offs in achieving maximum biodiversity across multiple biodiversity dimensions at any given location.